Different Approaches to Analyze Muscle Fat Replacement With Dixon MRI in Pompe Disease - Alonso-Jiménez, Alicia; Nuñez-Peralta, Claudia; Montesinos, Paula; Alonso-Pérez, Jorge; García, Carme; Montiel, Elena; Belmonte, Izaskun; Pedrosa, Irene; Segovia, Sonia; Llauger, Jaume; Díaz-Manera, Jordi (Frontiers in Neurology, 2021)
Quantitative MRI is an increasingly used method to monitor disease progression in muscular disorders due to its ability to measure changes in muscle fat content (reported as fat fraction) over a short period. Being able to objectively measure such changes is crucial for the development of new treatments in clinical trials. However, the analysis of the images involved continues to be a daunting task because of the time needed. Whether a more specific analysis selecting individual muscles or a global one analyzing the whole thigh or compartments could be a suitable alternative has only been marginally studied. In our study we compare three methods of analysis of 2-point-dixon images in a cohort of 34 patients with late onset Pompe disease followed over a period of one year. We measured fat fraction on MRIs obtained at baseline and at year 1, and we calculated the increment of fat fraction. We correlated the results obtained with the results of muscle function tests to investigate whether the three methods of analysis were equivalent or not. We observed significant differences between the three methods in the estimation of the fat fraction at both baseline and year 1, but no difference was found in the increment in fat fraction between baseline and year 1. When we correlated the fat fraction obtained with each method and the muscle function tests, we found a significant correlation with most tests in all three methods, although in most comparisons the highest correlation coefficient was found with the analysis of individual muscles. We conclude that the fastest strategy of analysis assessing compartments or the whole thigh could be reliable for certain cohorts of patients where the variable to study is the fat increment. In other sorts of studies, an individual muscle approach seems the most reliable technique.